Sedimentology of an Upper Ordovician (late Katian-Hirnantian) deep shelf mudstone exposure preceding massive sea level drop - Mount Ålleberg, Västergötland, Sweden - Thomas, Russell, author; Egenhoff, Sven, advisor; Ronayne, Michael, committee member; von Fischer, Joe, committee member (Colorado State University. Libraries, 2021)
The deposition of siliciclastic mudstones in a passive margin deep shelf environment has not been explored well in literature. The upper Ordovician succession at Mt. Ålleberg, Västergötland (southern Sweden) is such a succession mirroring sedimentation on Baltica's deep shelf just prior to a catastrophic sea-level draw-down during the Hirnantian Ice Age. The here presented only exposed section is 6.3 meter thick and consists mostly of siliciclastic mudstones interspersed with carbonates. Siliciclastic mudstones are subdivided by dominant clast material and size into four facies, namely fine- to medium-grained (1), carbonate-rich (2), silt- to sand-rich (3), and bioclastic-rich (4). The carbonates are divided into two facies; a carbonate mud- to wackestone (facies 5) seen throughout the section and a lithoclastic fossiliferous carbonate rudstone (facies 6) only observed at the top of the section. Facies 6 carbonate rudstone clasts are poorly sorted and the matrix contains geopetal cement. The idealized succession coarsens upward from facies 1 to facies 5 and excludes facies 6; this idealized succession is observed only once in the section. Siliciclastic mudstones as well as one carbonate (facies 5) contain sediment features and trace fossils of round mud-filled burrows, randomly oriented shells, Phycosiphon-like fecal strings, and generally massive texture. Siliciclastic mudstones are observed with irregular, non-continuous, normally graded laminae. The succession is interpreted as deposition on the low-inclined Baltica shelf reflecting a ramp-like setting mostly an outer shelf environment reaching into a mid-shelf setting. Sediment features and trace fossils are a result of bioturbating organisms and suggest the entire water column was at least suboxic to support benthic life. The irregular laminae observed in all mudstones are interpreted as storm beds and counters the notion that the carbonate-siliciclastic transition is a product of storm wave base interaction. Rounded clasts in the carbonate rudstone (facies 6) reflect significant transport of those grains, likely from more proximal settings, and also indicate up-slope erosion. The geopetal cements are interpreted as indicating subaerial exposure following deposition. The exposure is likely the result of a glacioeustatic sea-level drop associated with the Gondwana glaciation during the late Hirnantian or at the Ordovician-Silurian boundary.
Keywords: bioturbation; mudstones; subaerial; Hirnantian; Baltica; Ordovician